The effect of azoximer bromide (Polyoxidonium®) in patients hospitalized with coronavirus disease (COVID-19): an open-label, multicentre, interventional clinical study - Sergey V Efimov; Natallia V Matsiyeuskaya; Olga V Boytsova; Lyudmila Yu Akhieva; Elena I Kvasova; Francisco Harrison; Yulia S Karpova; Anton Tikhonov; Nadezhda F Khomyakova; Tim Hardman; Jean-François Rossi (BioExcel Publishing Ltd, 2021)
A clinical need for aetiotropic coronavirus disease (COVID-19) treatments is required. The immune modulator azoximer bromide (AZB; Polyoxidonium®) is indicated in Russia for use against acute viral infections and during remission. In this study, adults hospitalized with COVID-19 (n=32) received AZB and standard of care in an open-label, multicentre, interventional study. All patients were symptomatic; 22 had severe disease (National Early Warning Score ≥5) and required mechanical ventilation or respiratory support and 19 patients had co-morbidities. Patients received AZB 12 mg intravenously once daily for 3 days, then intramuscularly every other day (approximately ten injections) until discharge. The primary endpoint was the patient's clinical status (7-point Ordinal Scale; OS) on day 15 versus that at baseline. The mean duration of hospitalization was 20 days. All patients were alive and discharged with normal oxygen saturation (SpO2) with no secondary infections or delayed mortality reported by the end-of-study visit (on day 28-72). A decrease in the mean OS and National Early Warning Score values was observed following treatment with AZB. A decrease in OS score was marked in patients identified as severe. Both sets of patients achieved similar scores, which can be classified as an improvement by day 9-10; SpO2 levels trended to normalization over time. By day 11-12, all patients had a normal body temperature. Serum C-reactive protein levels decreased in patients with severe and mild disease. Most patients had signs of pneumonia at baseline (n=27), with the majority recovering by days 10-12. No major toxicities were observed. AZB was safe and well tolerated when administered in addition to standard of care treatment for COVID-19. Further randomized, placebo-controlled studies are needed to elucidate any potential therapeutic effect in COVID-19.